Womens’ mall patronage intentions : Impacts of attitude, subjective norm and self-efficacy in an Internationalized Shopping Centre - Toh, Evelyn Bee Hwa *; Selvan, Perumal (2016)
The study focuses on an Internationalized Shopping Centre in Malaysia. It is internationalized because it was originally owned and operated by a Malaysian conglomerate (Sunway Group) but was subsequently taken over by a Singaporean based group. The interesting phenomenon about this transformed shopping centre is the business of mergers and acquisitions by localized Singaporean MNCs. Hence, the study examines attributes of a shopping centre and is guided by the Theory of Planned Behaviour (TPB) model as well as literature on shopping centre patronage, seeking to investigate how the three constructs (attitude, subjective norm and perceived behavioural control) would influence womens’ intention to patronising a shopping centre. Data to be collected from a shopping centre (Sunway Pyramid) located in the Klang Valley, using the mall intercept method, will only be conducted on two weekends when the shopping centre is usually crowded. It was concluded that despite the constraints (internal and resources) in which women face, they would still have intention to patronise shopping centres and ultimately indulge in impulse purchasing.